Uncharted territory and extraordinary times: the SENCo's experiences of leading special education during a pandemic in England. (25th April 2021) - Middleton, Tristan; Kay, Lynda
Abstract : This research focuses on the impact of the context of Covid‐19 on the role of the SENCo in English schools. The SENCo's role is a contested field; however, the current Special Educational Needs Code of Practice identifies 11 key areas of SENCos' work. A widely distributed survey was used to access the voice of SENCos across the country, and received 26 responses. Data were analysed using a realistic evaluation framework to identify the impact of Covid‐19 on the work of the SENCo. The research indicated that practice in this context had changed in some key areas, and also identified three new aspects of the SENCo role. These point to the need to revise policy and guidance relating to the SENCo being part of the senior leadership team, providing emotional support for adults, and engaging in practical pedagogical activities.